"Helping Nemo!"-Using Augmented Reality and Alternate Reality Games in the Context of Universal Design for Learning - Nayia Stylianidou; Angelos Sofianidis; Elpiniki Manoli; Maria Meletiou-Mavrotheris (MDPI AG, 2020)
This article reports on the main experiences gained from a teaching intervention which utilised the alternate reality game 'Helping Nemo' in an augmented reality environment for formative assessment. The purpose of the study was to explore the ways in which the affordances arising from the combination of alternate reality games and augmented reality, situated in the context of Universal Design for Learning, might facilitate students' learning amongst the aspects of engagement, participation, and response to students' variability. The study took place in a public primary school located in a rural area of Cyprus. A second-grade class consisting of 24 students aged 7-8 years old was selected to comprise the sample. A qualitative research approach was adopted. The data collection methods included classroom observations and focus groups with the students. Findings gained from the teaching intervention suggest that the creation of a multimodal environment that draws on the principles of Universal Design for Learning and combines the affordances of alternate reality games and augmented reality for formative assessment contributes towards higher levels of engagement and participation in learning of all students, including bilingual students, students with learning disabilities, and students who are currently disengaged.